Autobiographic Narrative in the Drawings of Napachie and Annie Pootoogook - Tomaszewskska, Karolina (2012)
In June of 2005, Windows on Kinngait featuring drawings by Annie Pootoogook and Napachie Pootoogook had opened at the Feheley Fine Arts Gallery in Toronto. With this thesis I set out to compare these two art practices, focusing on how each artist approaches issues related to gender and how they tackle the motif of modernity through representations of landscapes (both indoor and outdoor) and objects, all of which convey much about the personal lives of these women. They will be examined in terms of how space, and the things that fill it, are utilized to convey an idea about personal representation. In order to understand the inventive drawing practices developed by Napachie and Annie, I will trace the changing status of drawing as a medium in relation to the printmaking tradition; I will also introduce some other artists from Kinngait (Cape Dorset) who have explored the tension between traditional and contemporary motifs in their work. In theoretical terms, I use Hertha Dawn Wong’s scholarship on forms of indigenous autobiography and the postcolonial concept of hybridity (as put forward by Homi Bhabha) to illuminate the 20th-century transformations in Inuit artmaking, as exemplified in the art of Napachie and Annie Pootoogook.